Vices and Virtues of Make in India in Indian Economy: A Case Study on Greensole (Global Journal of Management and Business Research, 2020)
The concept of #x201C;Make in India#x201D; is no less than a revolution in today#x2019;s time when the economy is facing so many challenges. Traditional means of progress can no longer satisfy the needs of development. For an overall and holistic development it is important to come forward with new ways of development and change. The concept of make in India is one such method or a way to bring about that change in the nation. Here, it should also be seen as to what are the pros and cons of this concept and is this campaign really viable? This paper aims at finding out answers to these questions: how will make in India help the economy in growing and what are the vices and virtues of the make in India campaign. It also tries to study how eco friendly ideas can create Make in India campaign a success through a case study on Green sole organization.
Keywords: make in india; development; economy; competitiveness